The Effect of Corporate Governance Mechanisms on Earnings Management in Malaysian Manufacturing Companies - Murad Ali Ahmad Al-Zaqeba; Abdul Hamid, S.; Nehad Ibrahim Ineizeh; Obada Jebreen Hussein; Ala Hussein Albawwat (AESS Publication, 2024)
Indexed by Scopus/ERA